2005
DOI: 10.1590/s0100-879x2005000200012
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of human herpesvirus 8 infection in children born to HIV-1- infected women in São Paulo, Brazil

Abstract: Human herpesvirus-8 (HHV-8) appears to be transmitted mainly by sexual contact. However, several studies suggest that in developing countries the infection may be acquired early in life by routes other than sexual transmission. The present study estimated the seroprevalence of HHV-8 in Brazilian children born to HIV-1-infected mothers. The serum samples were collected in a cross-sectional cohort study from 99 children born to HIV-infected mothers (median age 3.27 years; range 1.5-13.8 years) attending the outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
1
0
1
Order By: Relevance
“…The results of this study show that the rates of detection of HHV‐8 DNA in saliva were significantly higher in HIV‐infected individuals and their household members. The prevalence of HHV‐8 in this study is in accordance with previous studies that showed infection rates in Brazil ranging from 4.6 to 50% (6, 24, 29–32). The prevalence of HHV‐8 infection increases in HIV‐infected patients (33, 34).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study show that the rates of detection of HHV‐8 DNA in saliva were significantly higher in HIV‐infected individuals and their household members. The prevalence of HHV‐8 in this study is in accordance with previous studies that showed infection rates in Brazil ranging from 4.6 to 50% (6, 24, 29–32). The prevalence of HHV‐8 infection increases in HIV‐infected patients (33, 34).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of HHV‐8 in this study is in accordance with previous studies that showed infection rates in Brazil ranging from 4.6% to 50% (20–27). Some studies observed that HHV‐8 is more prevalent in saliva in HIV‐infected individuals than in non‐HIV‐infected individuals (26–28).…”
Section: Discussionsupporting
confidence: 92%
“…Although HHV-8 is also transmitted through sexual intercourse [Simpson et al, 1996], the high prevalence of antibodies among children reinforces the possibility of other routes of dissemination [Lennette et al, 1996;Biggar et al, 2000;Plancoulaine et al, 2000;Machado et al, 2005]. The high level of antibodies in Amerindians could be due possibly to vertical transmission of a virus which usually persists within the human host.…”
Section: Discussionmentioning
confidence: 99%